G-Log: a graph-based query language - Paredaens, J.; Peelman, P.; Tanca, L. (IEEE transactions on knowledge and data engineering, 1995)
We introduce G-Log, a declarative query language based on graphs, which combines the expressive power of logic, the modeling power of complex objects with identity and the representation power of graphs. G-Log is a nondeterministic complete query language, and thus allows the expression of a large variety of queries. We compare G-Log to well-known deductive database languages, and find that it is the only nondeterministic and computationally complete language that does not suffer from the copy-elimination problem. G-Log may be used in a totally declarative way, as well as in a "more procedural" way. Thus, it provides an intuitive, flexible graph-based formalism for nonexpert database users.< >